HUBUNGAN LAMA MENDERITA DENGAN KENYAMANAN FISIK PADA PASIEN PPOK DI RUANG PAVILIUN CEMPAKA RSUD JOMBANG - Maunaturrohmah, Agustina (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2018)
Chronic Obstructive Pulmonary Disease (COPD) is a disease characterized by airway limitations that is not fully reversible and can be prevented. Patients who experience shortness of breath will show some discomfort of bodily functions and limited independence, so patients tend to avoid daily physical activity that causes immobilization, the relationship of patients with social environments decreases. The aim of this study was to analyze the relationship between duration of suffering with physical comfort in patients with chronic obstructive pulmonary disease (COPD).The design of this study used a cross sectional approach. The population in this study were all patients in the Cempaka Pavilion Jombang Hospital treatment room with an average of 26 patients per month. The sample in this study was 20 respondents using simple random sampling technique. Data collection using a questionnaire. Processing data editing, coding, scoring, tabulating and analyzing data using the Spearman rho statistical test with alpha 0.05.The results showed that the duration of illness for 3-4 years was 10 respondents (50%), 1-2 years as many as 7 respondents (35%) and for 5-6 years as many as 3 people (15%). Physical comfort as many as 12 respondents (60%) felt comfortable and as many as 8 respondents (40%) felt uncomfortable. The results of statistical tests with Spearman rho obtained a value of p = 0.015 <alpha = 0.05 so that H1 was accepted.The conclusion in this study is that there is a relationship between the duration of suffering and physical comfort in patients with chronic obstructive pulmonary disease (COPD).Keywords: duration, suffering, physical, comfort, COPD